Aromatic Base Stacking in DNA: From ab initio Calculations to Molecular Dynamics Simulations - Sponer, J; Berger, I; Spačková, N; Leszczynski, J; Hobza, P (Journal of biomolecular structure & dynamics, 2000)
Abstract Aromatic stacking of nucleic acid bases is one of the key players in determining the structure and dynamics of nucleic acids. The arrangement of nucleic acid bases with extensive overlap of their aromatic rings gave rise to numerous often contradictory suggestions about the physical origins of stacking and the possible role of delocalized electrons in stacked aromatic π systems, leading to some confusion about the issue. The recent advance of computer hardware and software finally allowed the application of state of the art quantum-mechanical approaches with inclusion of electron correlation effects to study aromatic base stacking, now providing an ultimitate qualitative description of the phenomenon. Base stacking is determined by an interplay of the three most commonly encountered molecular interactions: dispersion attraction, electrostatic interaction, and short-range repulsion. Unusual (aromatic- stacking specific) energy contributions were in fact not evidenced and are not necessary to describe stacking. The currently used simple empirical potential form, relying on atom-centered constant point charges and Lennard-Jones van der Waals terms, is entirely able to reproduce the essential features of base stacking. Thus, we can conclude that base stacking is in principle one of the best described interactions in current molecular modeling and it allows to study base stacking in DNA using large-scale classical molecular dynamics simulations. Neglect of cooperativity of stacking appears to be the most serious approximation of the currently used force field form. This review summarizes recent developments in the field. It is written for an audience that is not necessarily expert in computational quantum chemistry and follows up on our previous contribution (Sponer et. al., J. Biomol. Struct. Dyn. 14, 117, (1997)). First, the applied methodology, its accuracy, and the physical nature of base stacking is briefly overviewed, including a comment on the accuracy of other molecular orbital methods and force fields. Then, base stacking is contrasted with hydrogen bonding, the other dominant force in nucleic acid structure. The sequence dependence and cooperativity of base stacking is commented on, and finally a brief introduction into recent progress in large-scale molecular dynamics simulations of nucleic acids is provided. Using four stranded DNA assemblies as an example, we demonstrate the efficacy of current molecular dynamics techniques that utilize refined and verified force fields in the study of stacking in nucleic acid molecules.
Keywords: Static Electricity; simulace molekulární dynamiky; vodíková vazba; statická elektřina; konformace nukleové kyseliny; Models, Molecular; Nucleic Acids; molekulární modely; Nucleic Acid Conformation; Molecular Dynamics Simulation; nukleové kyseliny; Hydrogen Bonding; DNA